2020
DOI: 10.1029/2020ja028119
|View full text |Cite
|
Sign up to set email alerts
|

Observational Evidence for the Role of Hall Conductance in Alfvén Wave Reflection

Abstract: Electromagnetic energy carried by magnetohydrodynamic modes is an important mechanism in the energy transfer between the magnetosphere and the ionosphere. Alfvén waves are known to carry field-aligned currents and thus play an important role in the dynamics of the ionosphere-magnetosphere coupling. The role of Hall conductance in this interplay has been explored in magnetohydrodynamic models of the ionosphere but has hitherto not been observed in situ. We use 5 years of observations from the Swarm mission to s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…For the unfiltered 16 Hz and first few SGLP filtered datasets, the average downward integrated Poynting flux is roughly 2.5 times larger than the equivalent upward for all IMF orientations. These results are consistent with the dominance of magnetospheric forcing to the ionosphere rather than vice versa (as a potential result of the neutral wind dynamo; Kelley et al, 1991), and with previous studies who observed lower magnitude upward Poynting fluxes statistically (e.g., Gary et al, 1995;Ivarsen et al, 2020;Keiling et al, 2003). At large SGLP filters (e.g., 40+ s/600+ km), the downward integrated Poynting flux is closer to 3 times larger than the upward for all IMF orientations.…”
Section: Solar Windsupporting
confidence: 91%
See 3 more Smart Citations
“…For the unfiltered 16 Hz and first few SGLP filtered datasets, the average downward integrated Poynting flux is roughly 2.5 times larger than the equivalent upward for all IMF orientations. These results are consistent with the dominance of magnetospheric forcing to the ionosphere rather than vice versa (as a potential result of the neutral wind dynamo; Kelley et al, 1991), and with previous studies who observed lower magnitude upward Poynting fluxes statistically (e.g., Gary et al, 1995;Ivarsen et al, 2020;Keiling et al, 2003). At large SGLP filters (e.g., 40+ s/600+ km), the downward integrated Poynting flux is closer to 3 times larger than the upward for all IMF orientations.…”
Section: Solar Windsupporting
confidence: 91%
“…Statistical patterns of Swarm derived upward Poynting flux, not sorted by the IMF orientation, can be found in Ivarsen et al. (2020).…”
Section: Swarm Data Processingmentioning
confidence: 91%
See 2 more Smart Citations
“…Using Swarm A magnetic and electric field measurements, Ivarsen et al. (2020) found a larger Alfvén wave reflection coefficient in the NH than in the SH. They interpreted this observation as a consequence of hemispheric asymmetry in the precipitation induced conductance, with the largest hemispheric asymmetry seen during local winter.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%